The effect of applying the ISO45001 occupational health and safety management system and poka yoke error prevention system on dimensioning the quality of work life: An applied study on the group of AlKronji Group of Beverages and Juices (Entrepreneurship Journal for Finance and Business, 2021)
The organizations' obtaining the ISO 45001 has a great role in providing a safe working environment for the organization. The organization’s implementation of the error prevention system contributes greatly to improving the quality of the organization’s products. On the other hand, providing the dimensions of the quality of work life in the institutions contributes greatly to the organization’s success and continuity It remains on the market.Hence the importance of the study, which aims to indicate the role of both the occupational health and safety systems and the error prevention system in providing dimensions of the quality of work life. The importance of the study is reflected in providing a practical framework that links the implementation of the ISO45001 Occupational Health and Safety Management System and the poka yoke error prevention system to the dimensions of the working life atmosphere. If the descriptive analytical approach was used, and based on the importance of the study, the study problem can be formulated. Does the application of the ISO45001 Occupational Health and Safety Management System standards and error prevention system contribute to providing quality work life dimensions?